Infertility disclosures among women, men and couples: a systematic literature review - Lim, Wai Ping Penny; Tham, Jen Sern; Osman, Mohd Nizam; Omar, Siti Zobidah (Universiti Putra Malaysia, 2025)
This review paper examines the disclosure of decision-making and coping mechanisms among women, men, and couples dealing with infertility. The PRISMA review method analyzes 13 articles published between 2000 and 2021. Five themes are identified: openness, topic, social support level, confrontation, and avoidance. Additionally, the paper integrates social exchange theory to understand better the dynamics of disclosure and support exchange among those navigating infertility. The study recommends the need for more research on men, acknowledging their often marginalized role and the difficulties they face in discussing infertility. The review concludes that coping strategies are crucial in combating the social stigma associated with infertility.